An investigation of organizational communication citizenship behaviors of faculty and staff at historically black colleges and universities - Rocker K; Kelly S; Croucher S (Taylor and Francis Group on behalf of the Eastern Communication Association, 2025)
Drawing on organizational citizenship behavior (OCB) and structurational divergence (SD), this study (n = 190) observes how SD and demographic variables predict OCBs among faculty and staff at historically Black colleges and universities (HBCUs). Stepwise regression revealed significant predictors for several OCB factors: salary, age, and tenure for conscientiousness; SD, age, and tenure for sportsmanship; salary for civic virtue; salary and attending an HBCU for courtesy; and salary, age, tenure, and attending an HBCU for altruism. This study highlights the role SD and demographic variables have in promoting OCB at HBCUs during a time when presidents/chancellors are tasked with issues surrounding declining funding, increased competition, and shifts in the pedagogical environment. Understanding these dynamics assists senior leadership in enhancing their approaches to leadership and governing the culturally unique HBCU environment.
Keywords: Organizational citizenship behaviors; structurational divergence; HBCU; PWI; organizational culture; organizational identity